SHAPE - Hackney, Peggy (Cena, 2020)
This article results from presentations at conferences in Germany and the United States in 1993 e 1994, which were later revised. The author discusses the notions of Form and Shape and its possible mean- ings in English language and in Laban / Bartenieff Movement Analysis System considering it as an in- dependent category of analysis. It discusses consen- sus and disagreements in the use of this material as well as its symbols or notation signs in different LMA programs. She presents suggestions for notation and to what differences Modes of Shape Change, Shape Qualities, General Shape Flow Baseline and Postur- al Shape Flow Support based on her teaching expe- rience in LMA programs. She also indicates when to use Shape based analysis. On presenting the back- ground of Shape category in LMA, she makes an invi- tation to deepen discussion as a mode of developing and changing shapes and wisdoms for a future use. Keywords Laban/Bartenieff Movement Analysis System. Shape. Modes of Shape Change. Shape Qualities. Notation Symbols.